2021
DOI: 10.1002/anie.202104986
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Pathway from CdSe Magic‐Size Clusters with Absorption Doublets at 373/393 nm to Clusters at 434/460 nm

Abstract: Divergent interpretations have appeared in the literature regarding the structural nature and evolutionary behavior for photoluminescent CdSe nanospecies with sharp doublets in optical absorption. We report a comprehensive description of the transformation pathway from one CdSe nanospecies displaying an absorption doublet at 373/393 nm to another species with a doublet at 433/460 nm. These two nanospecies are zero‐dimensional (0D) magic‐size clusters (MSCs) with 3D quantum confinement, and are labeled dMSC‐393… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(64 citation statements)
references
References 63 publications
(140 reference statements)
3
61
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thef ormer (MSC-A) exhibits distinct optical absorption peaking at ac onstant wavelength A expressed in nanometers (nm), while the latter (PC-A) is usually transparent at this wavelength Aa nd to longer wavelengths.T he MSCs and their counterpart PCs are quasi isomers and transform mutually via reversible intramolecular reorganization. Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1). ForaMSC-A to MSC-B transformation, the three steps are MSC-A to PC-A, PC-A to PC-B,and PC-B to MSC-B.However,the reported transformations are limited to those between two binary MSCs, [3][4][5][6][7][8][9][10] or between ab inary MSC and at ernary MSC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thef ormer (MSC-A) exhibits distinct optical absorption peaking at ac onstant wavelength A expressed in nanometers (nm), while the latter (PC-A) is usually transparent at this wavelength Aa nd to longer wavelengths.T he MSCs and their counterpart PCs are quasi isomers and transform mutually via reversible intramolecular reorganization. Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1). ForaMSC-A to MSC-B transformation, the three steps are MSC-A to PC-A, PC-A to PC-B,and PC-B to MSC-B.However,the reported transformations are limited to those between two binary MSCs, [3][4][5][6][7][8][9][10] or between ab inary MSC and at ernary MSC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1). ForaMSC-A to MSC-B transformation, the three steps are MSC-A to PC-A, PC-A to PC-B,and PC-B to MSC-B.However,the reported transformations are limited to those between two binary MSCs, [3][4][5][6][7][8][9][10] or between ab inary MSC and at ernary MSC. [1,2,5] Before the present study, transformations in ternary MSCs have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is established that colloidal semiconductor compound magic-size clusters (MSCs) have particular precursor compounds (PCs). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thef ormer (MSC-A) exhibits distinct optical absorption peaking at ac onstant wavelength A expressed in nanometers (nm), while the latter (PC-A) is usually transparent at this wavelength Aa nd to longer wavelengths.T he MSCs and their counterpart PCs are quasi isomers and transform mutually via reversible intramolecular reorganization. Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1).…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Fors emiconductor binary systems,a nI Ps ample typically contains av ariety of species,i ncluding the corresponding ME PCs, monomers (Mo), and fragments (Fr) (Scheme S2). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] After two binary IP samples of CdTea nd CdSe were mixed with each other, ternary CdTeSe MSC-399 was seen to evolve at room temperature when the mixture was incubated or placed in mixtures of toluene (Tol) and octylamine (OTA). [1,2] The formation of the counterpart PC for MSC-399, PC-399, occurred as described by the monomer substitution reaction given in Equation (1): [1] CdTe PC-371 þ CdSe ðMo=FrÞ)…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal semiconductor binary II–VI metal chalcogenide (ME) magic-size clusters (MSCs) and quantum dots (QDs) are expected to improve our understanding of the evolution of optical/electronic properties when the size increases from individual molecules toward extended bulk materials. It has long been acknowledged that MSCs and QDs have different optical properties. For example, MSCs have a relatively narrow-band optical absorption due to their tight size distribution. Due to structural stability, the absorption of each MSC species peaks at essentially a constant wavelength.…”
mentioning
confidence: 99%